Women farmers’ participation in the agricultural research process: implications for agricultural sustainability in Ethiopia - Annet A. Mulema; Wellington Jogo; Elias Damtew; Kindu Mekonnen; Peter Thorne (International Journal of Agricultural Sustainability, 2019)
Empowering women farmers to participate in agricultural research is a key strategy for sustainable agricultural development. Women empowerment has the potential to improve their roles in agricultural production while enhancing nutrition and food security. Although new agricultural development policies are focusing on improving women engagement in agriculture, there is limited literature on women empowerment in relation to agricultural research. This study used mixed methods to analyse women farmers’ participation in four stages of the agricultural research process – design, testing, dissemination, monitoring and evaluation. Two hundred and thirty individual interviews with women farmers and 16 focus group discussions with men and women farmers were conducted in four Woredas (districts) of Ethiopia. Quantitative data were analysed using binary and multivariate probit models. Qualitative data were analysed using line-by-line coding. The results showed that several empowerment indicator variables significantly (p ≤ .001) influenced women’s participation in different stages of agricultural research. Specifically, input in production decisions, autonomy in plot management, membership to farmer groups, and ability to speak in public enhanced women’s participation in different stages, in addition to access to information and extension services, education and land size. Cultural norms hindered women’s empowerment and engagement in research. To foster sustainable agriculture development, it’s important to integrate holistic and proactive gender perspectives into research strategies to increase women’s participation in farmer research groups, access information and knowledge, have voice and challenge constraining cultural norms and traditions.